The Oxford history of the laws of England. Volume VI, 1483-1558 - Baker, John H. (University Press, 2003)
This volume covers the years 1483-1558, a period of immense social, political, and intellectual changes, which profoundly affected the law and its workings. It first considers constitutional developments, and addresses the question of whether there was a rule of law under king Henry VIII. In a period of supposed despotism, and enhanced parliamentary power, protection of liberty was increasing and habeas corpus was emerging. The volume considers the extent to which the lawwas affected by the intellectual changes of the Renaissance, and how far the English experience differed from that of the Co